Representation of African-American People in E. O’Neil’s The Emperor Jones - Rasheed Ahmed, Khorsheed (Humanities Journal of University of Zakho, 2020)
In every nation’s literature in the world, a play or a playwright often becomes the most predominant one and plays an effective role in the contemporary society. Accordingly, The Emperor Jones by Eugene O’Neill, an American, is considered one of the best and the well-known masterpieces which are written in late 1920s. This study, entitled “Representation of African-American People in E. O’Neil’s The Emperor Jones”, attempts to examine the representations of African -American people in terms of socio-historical background, culture and tradition; language and belief in E. O'Neil's The Emperor Jones, in the light of African-American history through the main character who struggles to resist for being an emperor while denying his own identity as an Afro-American, and, through imitating his exploiter who eventually led him to represent his own ethnicity and people. The play depicts an image of African-American society historically through several hallucinations which happened within the mind of the main character.